Neonatal extracorporeal membrane oxygenation: practice patterns and predictors of outcome in the UK. Issue 2 (1st October 2008) - Karimova, A; Brown, K; Ridout, D; Beierlein, W; Cassidy, J; Smith, J; Pandya, H; Firmin, R; Liddell, M; Davis, C; Goldman, A
Abstract : Objective: To review the UK neonatal extracorporeal membrane oxygenation (ECMO) service and identify predictors of outcome. Design: Retrospective review of the national cohort. Patients and interventions: 718 neonates received ECMO for respiratory failure between 1993 and 2005. Measurements and results: Diagnoses were: 48.0% meconium aspiration syndrome (97.1% survivors), 15.9% congenital diaphragmatic hernia (CDH; 57.9% survivors), 15.9% sepsis (62.3% survivors), 9.5% persistent pulmonary hypertension (79.4% survivors), 5.6% respiratory distress syndrome (92.5% survivors) and 5.1% congenital lung abnormalities (24.3% survivors). The overall survival rate of 79.7% compared favourably with the worldwide Extracorporeal Life Support Organization (ELSO) Registry. Over the period of review, pre-ECMO use of advanced respiratory therapies increased (p<0.001), but ECMO initiation was not delayed (p = 0.61). The use of veno-venous (VV) ECMO increased (p<0.001) and average run time fell (p = 0.004). Patients treated with VV ECMO had a survival rate of 87.7% compared with 73.4% in the veno-arterial (VA) ECMO group; only 42.4% of those needing conversion from VV to VA ECMO survived. In non-CDH neonates, lower birth weight, lower gestational age, older age at ECMO and higher oxygenation index (OI) were associated with increased risk of death. In CDH neonates, lower birth weight and younger age at ECMO were identified as risk factors for death. Conclusion: The UK neonatal ECMO service achieves good outcomes and with overall survival rate reaching 80% compares favourably with international results. Advanced respiratory therapies are used widely in UK ECMO patients. Identification of higher OI and older age at ECMO as risk factors in non-CDH neonates reinforces the importance of timely referral for ECMO.